Efficacy of plasma exchange in anti-MDA5-positive dermatomyositis with interstitial lung disease under combined immunosuppressive treatment. (10th April 2020) - Shirakashi, Mirei; Nakashima, Ran; Tsuji, Hideaki; Tanizawa, Kiminobu; Handa, Tomohiro; Hosono, Yuji; Akizuki, Shuji; Murakami, Kosaku; Hashimoto, Motomu; Yoshifuji, Hajime; Ohmura, Koichiro; Mimori, Tsuneyo
Abstract: Objectives: Rapidly progressive interstitial lung disease (RP-ILD) with poor prognosis often accompanies anti-melanoma differentiation-associated gene 5 (MDA5)-positive DM. Combined immunosuppressive therapy, including glucocorticoids, calcineurin inhibitors and intravenous cyclophosphamide (IVCY) is reportedly effective in DM with RP-ILD, but some patients remain resistant to therapy. We examined the utility of plasma exchange (PE) in such intractable cases and investigated the prognostic factors of the disease. Methods: Thirty-eight anti-MDA5-positive DM-ILD patients who received the combined immunosuppressive therapy were retrospectively reviewed. Their serum cytokines were evaluated by multiplex assay before treatment. The patients were divided into two groups: those who achieved remission without exacerbation of respiratory dysfunction ( n  = 25, group A) and those who progressed to hypoxemia during the treatment ( n  = 13, group B). Results: PE was carried out in eight group B patients, but none of group A. Five of the eight treated with PE survived, while the five untreated patients died ( P  =0.04). Higher neutrophil lymphocyte ratio, higher serum ferritin, hypoxemia, high-resolution computed tomography (HRCT) score before treatment and increase of Krebs von Lungen-6 (KL-6) in the first 4 weeks of the treatment were the prognostic factors for disease progression. Serum cytokines such as IL-1, IL-6, IL-8, IL-10, IL-12p70, IL-18 and sCD163 levels were higher in group B than group A. Conclusion: PE should be an effective adjuvant treatment in anti-MDA5-positive DM with RP-ILD. Assessment of basal laboratory tests or monocyte/macrophage-derived cytokines and the increase of KL-6, HRCT score and hypoxemia may help us to predict intractable cases and to make early treatment decisions regarding PE in anti-MDA5-positive DM.